Application of Electrocoagulation in Stabilizing pH and Removing Pollutants from Domestic and Urban Wastewater Using Aluminum Electrodes - Kaloka, Ardista Izdhihar; Faizah, Nurul; Arifin, Rizal; Aulia, Anisa Fatma; Putra, Muhammad Benaldo Anugrah; Wati, Ni'mah; Prayadi, Icha Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study investigates the application of electrocoagulation using aluminum electrodes to stabilize pH and remove pollutants from various real wastewater sources in Surabaya, Indonesia, including laundromats, fast food restaurants, campus canteens, mechanical workshops, and tofu industries. A batch-mode electrocoagulation process was conducted using 10 A of current over 60 minutes, and the performance was evaluated based on pH changes, turbidity, and Total Suspended Solids (TSS) removal. The highest TSS removal efficiency of 98% was observed in machine shop wastewater, while laundromat samples also achieved high performance with 97% reduction. Electrocoagulation demonstrated strong pH stability in effluents with buffering compounds such as those from campus canteens and workshops, whereas fluctuating pH and turbidity levels were found in tofu and fast-food effluents, indicating the need for process optimization. Turbidity decreased significantly across all samples, confirming effective floc formation during electrolysis. The findings confirm that electrocoagulation is a promising method for treating both domestic and urban wastewater. However, integrating additional processes such as adsorption or filtration is recommended to enhance performance for complex wastewater compositions and ensure compliance with discharge standards.